Evaluation of the mercury exposure of dental amalgam patients by the Mercury Triple Test. Issue 6 (18th May 2004) - Hansen, G; Victor, R; Engeldinger, E; Schweitzer, C
Abstract : Aims: To establish and analyse reference data for the mercury burden of patients with and without amalgam fillings. Methods: Atomic absorption spectroscopy was used to quantify Hg concentrations in the scalp hair and urine (before and after application of dimercaptopropane sulphonate), and Hg release from dental amalgams (using a newly developed, amalgam specific chew test), in 2223 subjects. Results: 50th centiles were 1.3 μg Hg/g creatinine in basal urine, 32 μg Hg/g creatinine after DMPS application, 454 ng Hg/g in hair, and 27 μg Hg per g of chewing gum, which corresponds to about 1 μg Hg released per minute of chewing. Total Hg intake (from ambient air, drinking water, food, and amalgams) of most patients is well below the provisioned tolerable weekly intake (PTWI) defined by the WHO, unless extremely Hg rich food is consumed on a regular basis. However, for patients exceeding the 75thcentile in chew tests, total Hg intake exceeds the PTWI by about 50%, even at the low limit of intake from food. In the absence of occupational exposure, significant Hg release from dental amalgams is a necessary but insufficient condition to obtain a high long term body burden. After removal of dental amalgams, chew tests no longer exhibit oral Hg exposure, while basal urine Hg content and DMPS induced excretion display a exponential decrease (half life about 2 months in both cases). Conclusions: A standardised procedure for evaluation of the magnitude and origin of the Hg burden of individuals has been developed, which, by comparison with the database presented here for the first time, can serve as a diagnostic tool.